2008
DOI: 10.1902/jop.2008.070476
|View full text |Cite
|
Sign up to set email alerts
|

Bone Formation Following Implantation of Bone Biomaterials Into Extraction Sites

Abstract: All sites revealed good primary stability at implant insertion and proper implant rigidity at abutment placement, indicating that early implant osseointegration was not influenced by the application of bone biomaterials used in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 21 publications
2
48
0
Order By: Relevance
“…These procedures are based on the use of graft materials, such as DFDBA, bioactive glass or deproteinized natural bovine bone 2,4,6,8,12,16,[34][35][36] . Resorption, osseous integration/organization and soft tissue encapsulation can be observed 29 , depending on the material properties and the size and shape of the inserted graft particles.…”
Section: Discussionmentioning
confidence: 99%
“…These procedures are based on the use of graft materials, such as DFDBA, bioactive glass or deproteinized natural bovine bone 2,4,6,8,12,16,[34][35][36] . Resorption, osseous integration/organization and soft tissue encapsulation can be observed 29 , depending on the material properties and the size and shape of the inserted graft particles.…”
Section: Discussionmentioning
confidence: 99%
“…The use of mineralized and demineralized allografts has been reported in numerous studies with acceptable outcomes. Molly et al (3) reported that allografts provide a scaffold for the blood clot, supporting osteogenic cells from the bone wall, which may enhance the quantity and quality of the resulting bone and aid in obtaining successful treatment outcomes with dental implants.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that a biodegradable scaffold in the bone socket would ensure healing of the bone socket without significant resorption or collapse which may complicate future implant placement. [2,4] Results indicate that scaffolds showed a stable pH during degradation. This is due to the ability of magnesium hydroxide to neutralize acidic monomers of the degradation.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Grafting materials are widely used as bone biomaterials to prevent collapse of bone walls and to facilitate future implant placement. [2][3][4] Various graft materials such as dried freeze-dried bone, deproteinized natural bovine bone mineral, hydroxyapatite (HA), β-tricalcium phosphate (β-TCP), bioglass, and calcium sulfate were used with varying success. [5] However, some of these materials are either non-resorbable or require longer time to resorb than the healing period of extraction socket and may interfere with the new bone formation.…”
Section: Introductionmentioning
confidence: 99%